Parental Divorce and In-School Adolescents’ Interpersonal Relationship in Egor Local Government Area, Edo State - ADUBALE, Andrew Agimhenlen; OSAGHALE, Omonye (Ilorin Journal of Education, 2024)
The study investigated the influence of parental divorce on secondary school students’ interpersonal relationship in Benin Metropolis. Descriptive survey design was adopted for the study. A sample size of two hundred and sixty-one (261) from 10 co-educational schools was used for the study. A structured questionnaire titled Parental Divorce and Interpersonal relationship Questionnaire (PDIRQ) was used to obtain information from the respondents. The psychometric properties of the instrument were established, the reliability coefficient value of .785 was obtained using Cronbach Alpha method. The data collected were analysed using descriptive statistics of mean and standard deviation and independent sample t-test. The findings revealed that parental divorce has no major influence on the students’ interpersonal relationship. Similarly, regardless of sex and age, parental divorce was not found to have any significant influence on the students. Based on the findings, it was recommended that the existing co-parenting of extended family system that appears to help in the reduction of the negative impact of divorce on children in Africa and Benin City, Edo State in particular should be sustained. Besides, school counsellors and administrators should continue to assist students of divorce parents to adjust adequately in school.